HOUSEHOLD ACCOUNTING IN THE WAHDAH ISLAMYAH MOSLEM COMMUNITY - Husniar,; Ratna Ayu Damayanti,; Andi Kusumawati, (International Journal of Innovations in Engineering Research and Technology, 2021)
This study aims to explore the phenomenon of household accounting in the Wahdah Islamiyah community using a phenomenological approach by interpreting Surah An-Anisa on the accounting of households. The data in this study were obtained by conducting deep interviews and analyzing documents or literatures. The informants in this study were members of Wahdah Islamiyah households in West Sulawesi. The results show that the informants implement accounting management in the household, but for reporting specifically it has not been carried out. Implementing accounting in the household based on the Sharia perspective is important on the rationale that the wealth or income obtained will feel a blessing by making more directed expenditures. Asset management based on an Islamic perspective sourced from the Qur'an and Sunnah will be beneficial because it makes them strong with piety and trust.